Processes of Inclusion and Exclusion in the Sphere of Prosumerism - Roberta Paltrinieri; Piergiorgio Degli Esposti (Future Internet, 2013)
The term prosumer, first introduced by Toffler in the 1980s, has been developed by sociologists in response to Web 2.0 (the set of technologies that has transformed a predominantly static web into the collaborative medium initially envisaged by Tim Berners-Lee). The phenomena is now understood as a process involving the creation of meanings on the part of the consumer, who re-appropriates spaces that were dominated by institutionalized production, and this extends to the exploitation of consumer creativity on the production side. Recent consumption literature can be re-interpreted through the prosumer lens in order to understand whether prosumers are more creative or alienated in their activities. The peculiar typology of prosumption introduced by Web 2.0 leads us to analyze social capital as a key element in value creation, and to investigate its different online and offline forms. Our analysis then discusses the digital divide and critical consumerism as forms of empowerment impairment.